Исследование структуры и свойств сплава ВК8 с добавками наноразмерного карбида вольфрама - Панов, В.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
On standard technology alloys ВК8 with the additive 1,5–4,0 % nanostructure carbide
tungsten have been prepared. Have been investigated their structure and properties. It has been shown, that introduction nanostructure carbide tungsten practically does not render influence on properties and structure of alloy ВК8.